Four new genera of Nearctic Cecidomyiidae (Diptera) for species previously incorrectly placed - Gagné, Raymond J. (Zootaxa, 2013)
Four new genera belonging to the tribe Dasineurini (Diptera: Cecidomyiidae: Lasiopteridi) are described for previously incorrectly placed species. The new genera are: Cembrotia Gagné, type species Janetiella coloradensis Felt; Cupressatia Gagné, type-species Janetiella siskiyou Felt; Strobilotia Gagné, type species Phytophaga carpophaga Tripp; and Rhizocecis Gagné, type species Cecidomyia rhois Coquillett. Resulting new combinations are: Cembrotia coloradensis (Felt), Cupressatia siskiyou (Felt), Cupressatia thujae (Hedlin), Strobilotia carpophaga (Tripp) and Rhizocecis rhois (Coquillett).